Atención al cliente en el Comercial “Solano” de la ciudad de Babahoyo, periodo 2023. - Martínez Tarira, Noe Moisés (2024)
Customer service plays a crucial role in the success of any company, and the case study of the paint company "SOLANO" in the city of Babahoyo during the period 2022 offers a unique insight into how effective management of this aspect can Make a Difference. This study examines SOLANO's customer service strategy and execution, focusing on its commitment to excellence and customer satisfaction. The commercial has demonstrated a firm commitment to quality in its products and services, but its emphasis on customer service has been especially notable. During the study period, the company has implemented a proactive approach to understand the needs and expectations of its customers in the paint sector. Staff training has been a priority for SOLANO, with an emphasis on empathy and problem solving. Customer service representatives have received extensive training on products, colors and applications, which has significantly improved the ability to provide expert advice. This proactive approach has not only strengthened the relationship with existing clients, but has also contributed to the acquisition of new clients through positive referrals. Furthermore, SOLANO has integrated modern technologies to improve customer experience. The implementation of online platforms and mobile applications has made it easier for customers to place orders, inventory inquiries and track deliveries. This technological approach has optimized operational efficiency and contributed to a more satisfying customer experience. SOLANO's social commitment through community programs and local sponsorships, the company has built an image of social responsibility that resonates with its customers in Babahoyo.